Pendekatan Hexagon Fraud dalam Mendeteksi Kecurangan Laporan Keuangan dengan Komite Audit sebagai Moderasi - Leonald Franstiyanto; Juniati Gunawan (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2025)
This study analyzes the influence of six elements in the Hexagon Fraud framework on financial statement fraud, while also examining the moderating role of the audit committee. The elements investigated include pressure (financial stability), capability (change in director), opportunity (nature of industry), rationalization (total accruals to total assets), arrogance (family relationships), and collusion (CEO duality). Data were obtained from the financial reports of food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The analysis employed multiple regression and interaction tests for moderation effects. The results indicate that pressure, capability, opportunity, and rationalization have a significant positive effect on financial statement fraud. In contrast, arrogance and collusion were found to be insignificant. The audit committee failed to moderate the relationship between fraud elements and financial statement fraud effectively and, in some cases, even reinforced the relationship. These findings highlight weaknesses in internal monitoring structures, suggesting that the existence of audit committees is not matched by adequate quality, independence, or competence. Practically, firms are advised to strengthen the audit committee’s role substantively rather than symbolically. Regulators are also encouraged to tighten oversight and establish minimum qualification standards for audit committees, particularly in industries with high fraud risk. Abstrak Penelitian ini menganalisis pengaruh enam elemen dalam pendekatan Hexagon Fraud terhadap kecurangan laporan keuangan, serta menguji peran komite audit sebagai variabel moderasi. Elemen yang dianalisis mencakup pressure (financial stability), capability (pergantian direktur), opportunity (karakteristik industri), rationalization (total akrual terhadap aset), arrogance (relasi keluarga), dan collusion (CEO duality). Data diperoleh dari laporan keuangan perusahaan subsektor makanan dan minuman di BEI periode 2022–2024, dengan analisis regresi berganda dan uji interaksi moderasi. Hasil menunjukkan bahwa pressure, capability, opportunity, dan rationalization berpengaruh signifikan terhadap fraud. Sebaliknya, arrogance dan collusion tidak signifikan. Komite audit terbukti tidak mampu memoderasi hubungan elemen-elemen fraud secara efektif, bahkan cenderung memperkuatnya dalam beberapa kasus. Temuan ini menunjukkan kelemahan struktur pengawasan internal, di mana keberadaan komite audit belum diiringi kualitas, independensi, dan kompetensi yang memadai. Implikasi praktisnya, perusahaan perlu memperkuat peran komite audit secara substansial, bukan hanya formal. Regulator juga disarankan memperketat pengawasan serta menetapkan standar kualifikasi minimum bagi komite audit, khususnya di industri dengan risiko fraud tinggi. Kata Kunci: Hexagon Fraud, Kecurangan Laporan Keuangan, Komite Audit